2019
DOI: 10.1002/jemt.23423
|View full text |Cite
|
Sign up to set email alerts
|

Presence of voids after warm vertical compaction and single‐cone obturation in band‐shaped isthmuses using micro‐computed tomography: A phantom study

Abstract: The present micro‐computed tomography (micro‐CT) study compared the presence of voids in the band‐shaped isthmuses obturated by warm vertical compaction (WVC) and single‐cone (SC) techniques. Twenty mesial roots from mandibular first molar teeth showing a band‐shaped isthmus were selected and assigned into two groups based on their preoperative anatomical dimensions (n = 10), according to the filling technique: WVC or SC. Post‐filling micro‐CT scanning was performed. The percentage volume of root canal filling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…We showed that the technique was more beneficial to obturate the root canal with less void formation compared to warm vertical compaction. However, in contrast to our study, a considerable number of recent studies have reported that the filling quality of the SC technique was not inferior but instead superior to other techniques, such as warm vertical compaction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. While reviewing the papers, we recognized that all the studies were performed only using microcomputed tomography (μCT) but did not observe the sectioned tooth specimens using a microscope.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We showed that the technique was more beneficial to obturate the root canal with less void formation compared to warm vertical compaction. However, in contrast to our study, a considerable number of recent studies have reported that the filling quality of the SC technique was not inferior but instead superior to other techniques, such as warm vertical compaction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. While reviewing the papers, we recognized that all the studies were performed only using microcomputed tomography (μCT) but did not observe the sectioned tooth specimens using a microscope.…”
Section: Introductioncontrasting
confidence: 99%
“…However, in terms of void formation, a couple of studies, including ours, reported that the SC technique might be inferior to other techniques, such as the core-carrier method or vertical compaction [ 7 , 19 ]. Nevertheless, a significant number of studies showed that the SC technique did not generate more voids compared to other methods, and thus there are still controversies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, in the present study, we reproduced the experiment using a newly launched zirconium-oxide-containing premixed calcium silicate sealer (Endoseal TCS) with similar teeth and protocol.…”
Section: Discussionmentioning
confidence: 99%
“…However, the single‐cone technique was used in this study to allow direct comparison between Bio‐C and AH Plus since this technique has less operator influence (Heran et al, 2019). Previous studies used the single‐cone technique to evaluate the filling capacity in different root canal morphologies, such as straight root canals (Wang et al, 2018), oval root canals (Celikten et al, 2016), root canals with isthmus (Keleş & Keskin, 2020), and mesial canals of mandibular molars (Heran et al, 2019). Nevertheless, this is the first study using the single‐cone technique to evaluate the filling ability of endodontic sealers in flattened root canals.…”
Section: Discussionmentioning
confidence: 99%
“…Micro‐CT is a widely used method for assessing the filling quality of root canals (Celikten et al, 2015; Celikten et al, 2016; Keleş & Keskin, 2020), due to its possibility of three‐dimensional analyzes with high definition (Celikten et al, 2016). The X‐ ray interaction is determined by the material radiopacity (Bouxsein et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation